The Influence of Character Education on the Ethics of 5th-Grade Students at SDN 002 Pasar Usang Baserah, Kuantan Singingi Regency: Pengaruh Pendidikan Karakter Terhadap Etika Siswa Kelas V SDN 002 Pasar Usang Baserah Kabupaten Kuantan Singingi - Nabila Rahmadani; Muhamad Nukman (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study aims to examine the influence of character education on the ethics of 5th-grade students at SDN 002 Pasar Usang Baserah, Kuantan Singingi Regency. This research employs a quantitative approach with a survey method, involving 30 students selected through census sampling. Data were collected using a validated and reliable questionnaire. The results indicate that character education significantly influences student ethics. The majority of students are in the moderate category of character education, positively impacting their ethics. Thus, character education is proven to be crucial in shaping students' ethics, and strengthening this program in schools can enhance students' ethical behavior.